Serangan Hipoksia pada Orang Dewasa: Laporan Kasus - Perdana, Angga Putra; Tantri, Rossiana (PT Kalbe Farma Tbk., 2025)
Introduction: Hypoxic spells are serious and potentially fatal complications of cyanotic congenital heart disease. These events typically occur in children and are extremely rare in adults. They are caused by a sudden reduction in pulmonary blood flow, leading to severe hypoxia, cyanosis, seizures, and even death. Although rare, hypoxic spells should be considered as a differential diagnosis in adult patients presenting with hypercyanotic crises, particularly those without a known history of congenital heart disease. Case: A 20-year-old woman presented with worsening shortness of breath and cyanosis over the past two hours. She had a lifelong history of recurrent cyanosis, a habit of squatting during episodes of breathlessness, and limited physical activity but had never been diagnosed with congenital heart disease. Electrocardiography revealed right axis deviation and right ventricular hypertrophy, while a chest X-ray showed cardiomegaly with a boot-shaped heart silhouette. A hypoxia test supported the suspicion that her hypoxia was cardiac in origin. Initial management included the knee-chest position, highflow oxygen therapy, intravenous fluids, morphine, and norepinephrine to increase systemic vascular resistance. Subsequent echocardiography confirmed pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries (PA + VSD + MAPCAs), a rare variant of tetralogy of Fallot. Conclusion: Hypoxic spells in adults are extremely rare and often underrecognized, especially in resource-limited settings. Rapid diagnosis and early intervention are crucial to improving outcomes. Referral to a specialized cardiac center is essential for comprehensive evaluation and definitive treatment planning.